Politeness in Tshivenda - Nemukula, Ndishavhelafhi Alpheus (My University, 2002)
Refer to document
Thesis (M. A. (African Languages)) -- University of the North, 2002
Keywords: Venda language; Politeness; Politeness (Linguistics); Grammar, Comparative and general -- Honorific; Courtesy; Venda language